A Comparison of Comprehensive HIV/AIDS Knowledge Among Women Across Seven Post-Soviet Countries - Hakim Zainiddinov; Nazim Habibov (University Library System, University of Pittsburgh, 2018)
Introduction: Post-Soviet countries of Eastern Europe and Central Asia have witnessed a recent growth of HIV infection through heterosexual transmission. Women's low levels of knowledge about HIV prevention and transmission methods have been found to account for the higher female-to-male ratio among cases infected through the heterosexual route. This cross national comparison study assessed comprehensive HIV/AIDS knowledge and its key determinants among women of seven post-Soviet countries and identified which countries face the highest levels of risk due to the low levels of HIV/AIDS awareness. Methods: Study data were obtained from the third wave of the Multiple Indicator Cluster Surveys (MICS3) (conducted in 2005 and 2006), nationally representative samples of women aged 15-49 years. Data on HIV/AIDS knowledge were analyzed for women in Kazakhstan (N=14,310), Kyrgyzstan (N=6,493), Tajikistan (N=4,676), Uzbekistan (N=13,376), Belarus (N=5,884), Ukraine (N=6,066), and Georgia (N=7,727) using descriptive statistics and ordinary least squares (OLS) regressions. Results: We found that the percentage of women who could correctly identify all five modes of HIV/AIDS transmission and prevention was highest in Eastern European countries of Belarus (34.98%) and Ukraine (31.67%). Across all countries, the strongest predictors of comprehensive HIV/AIDS knowledge were age, education, and region of residence. Marital status, area of residence (urban vs. rural), and household wealth were significant predictors for several countries. Conclusion: High rates of comprehensive HIV/AIDS knowledge were found among women of Belarus and Ukraine. To reduce the spread of HIV in the region, programs promoting comprehensive HIV/AIDS knowledge for women of younger ages and with lower education are recommended.